26.7k views
6 votes
^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^-example-1

1 Answer

12 votes

Explanation:

expression

y = x² + 5

• according to Option 1

x = 0,1,2

y = 5,10,15

now,

5 = 0² + 5 → 5 = 5 ✓

10 = 1² + 5 → 10 = 1 + 5 → 10 ≠ 6

15 = 2² + 5 → 15 = 4 + 5 → 15 ≠ 9

therefore, Option 1 is incorrect

• now, according to option 2

x = 0,1,2

y = 5,6,9

now,

5 = 0² + 5 → 5 = 0 + 5 → 5 = 5

6 = 1² + 5 → 6 = 1 + 5 → 6 = 6

9 = 2² + 5 → 9 = 4 + 5 → 9 = 9

therefore, Option 2 is correct

• according to option 3

x = 0,1,2

y = 1,2,4

now,

1 = 0² + 5 → 1 ≠ 5

2 = 1² + 5 → 2 = 1+6 → 2 ≠ 6

4 = 2² + 5 → 4 = 4 + 5 → 4 ≠ 9

therefore, option 2 is correct

Hope this answer helps you!

User Satish Dhiman
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.